Grading Assessment of Energy Index Considering Equipment Tolerance Characteristics - Xingguan FAN; Yonghai XU; Chunhao NIU; Siying DENG (Zhongguo dianli)
Considering the influence of user equipment's voltage tolerance characteristics on the assessment results, a system-side voltage sag grading assessment method is proposed to improve the energy index, which considers the equipment's tolerance characteristics. Firstly, an analysis is made of the comparison benchmark value of the energy index and the insufficient description of the difference in severity of the sag events in the uncertain area; And then, the comparison benchmark value and weight coefficient are constructed based on the voltage tolerance curve, and an improved energy index evaluation model is built to grade the severity of the sag event; Finally, the proposed method is used to analyze 24 voltage sag events occurring at a monitoring node, which have proved the rationality and effectiveness of the proposed method. The proposed method can be used for voltage sag assessment and governance of the actual power systems.